ASSESSMENT OF THE ROLE OF IL-17A IN RHEUMATOID ARTHRITIS PATIENTS; IN SULAYMANIYAH GOVERNORATE - Tofiq, Dana Mohammed; Merza, Raouf Rahim (European Scientific Journal, ESJ, 2015)
Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by joint swelling and tenderness, with destruction of synovial joints, leading to severe disability and premature mortality. The etiology and pathogenesis of RA remain unknown, it is generally considered an autoimmune pathology in which autoreactive T cells of pathogenic potential, such as Th1 and Th17 cells, are thought to play an important role. Th17 cells selectively produce the signature cytokines such as IL-17, IL-21 and IL-22, and have been demonstrated to play a critical role for the chronic inflammatory response and subsequent tissue damage in the affected joints. Objectives: To assess the role of IL-17A in RA; by estimation of the serum IL-17A levels in RA and apparently healthy controls, and assessing the association of serum IL-17A levels with disease activity and severity measured by DAS-28 by ESR. Patients and Methods: Cross-sectional analytic study carried out in the division of rheumatology/Shaheed Hemin general hospital, in Sulymaniyah city from (January 2015 to September 2015); on 45 RA patients; and 45 age and gender matched apparently healthy controls. Measurements of serum IL- 17A were done for both patients and controls by ELISA according to the manufacturer’s instructions. Disease activity was determined in the patients; according to DAS-28 by ESR. Results: A significant association was observed between serum IL-17A level and RA (p<0.001). There was a significant difference in serum IL-17A levels among RA patients on non-biological therapy and controls (p<0.001), also there was a significant difference in serum IL-17A levels among RA patients on biological therapy and controls (p<0.001), and no significant difference was observed between the serum levels of IL-17A of RA patients on biological therapy and those on non-biological therapy (p=0.4), There was a significant association between serum IL-17A level and active RA disease (p<0.001). Conclusions: Serum IL-17A has a diagnostic value in RA, demonstrated by significant differences in serum IL-17A levels of RA patients and controls. Elevated serum IL-17A levels in RA patients parallel the degree of disease activity and severity. This may highlight the usefulness of IL-17A as a possible biomarker for more aggressive joint involvement and damage, giving it an important prognostic and predictive value.